Effectiveness, barriers, and facilitators of overweight and obesity prevention strategies in Latin America; a scoping review and qualitative study in ColombiaResearch in context - Gabriela V. Proaño; Lina Marcela Rodriguez Moreno; Maria Jacquelinne Arciniegas; Niliarys Sifre-Acosta; Carlos Espinal; Rajiv Chowdhury; Luis Jorge Hernández Flórez; Cristina Palacios (The Lancet Regional Health. Americas, 2024)
Summary: Background: This project aimed to synthesize the quantitative/qualitative evidence on the effectiveness of overweight/obesity prevention strategies implemented in Colombia and their barriers and facilitators. Methods: A scoping review was conducted by searching PubMed, SciELO, Scopus, and the grey literature (2012–2023). In-depth interviews were also conducted among key stakeholders on their perception of these strategies’ effectiveness, barriers, and facilitators. Findings: 26 records were included; four studies found positive changes in weight/body mass index, five found positive changes in physical activity, two found positive changes in food intake, and four found positive changes in healthy lifestyle knowledge, perception, attitudes, and habits. The main barrier reported was the obesogenic environment, and the facilitators were program flexibility and community engagement. Eighteen interviews were conducted (one interview per strategy); the main barriers reported were political, lack of evaluation access, economic situation, and lack of articulation; the main facilitators were incorporating the strategy into policies, articulation with stakeholders, and strong oversight. Interpretation: Moderate evidence indicates that these strategies positively impact outcomes related to overweight/obesity in Colombia, but more long-term studies are needed for overweight/obesity reduction. Lack of (1) evaluation and resources (barriers), (2) incorporation into policies (facilitators), and (3) strong stakeholder coordination (facilitators) was identified. Funding: Global Health Consortium, Department of Global Health, FIU.